Causal effects of microglia‐mediated innate immune responses in the pathogenesis of c9orf72 frontotemporal dementia and amyotrophic lateral sclerosis. (December 2021) - Trageser, Kyle J; Smith, Chad; Sebastian, Maria; Iqbal, Umar Haris; Wu, Henry; Rahim, Md Al; Pasinetti, Giulio Maria
Abstract: Background: The most common monogenic cause of frontotemporal dementia and amyotrophic lateral sclerosis (FTD/ALS) are G4 C2 repeat expansions in the c9orf72 gene. Aggregations of dipeptide repeat proteins (DPR) produced by these expansions have toxic effects on cellular homeostasis, coinciding with neuroinflammation and cell death. Glycine‐Arginine (GR) aggregates are significantly present in regions of the brain impacted by FTD/ALS. Here, we demonstrate the causal role of microglia mediated innate immune responses in the pathogenesis of FTD/ALS and identify the NLRP3 inflammasome as a therapeutic target for FTD/ALS. Methods: Wild‐type C57BL6/J and Nlrp3 deficient ( Nlrp3 ‐/‐ ) mice were transfected via intracerebroventricular injection with either AAV9‐GFP or AAV9‐GFP(GR)100 . At 14 weeks, animals were tested for motor function and memory. Cortical tissue (CTX) was dissected for analysis. Microglia density and activation were assessed in vivo by immunofluorescence for Iba1 and Sholl analysis. ELISA for IL‐1β was performed and levels of active caspase‐1 was measured via western blot. To investigate a mechanism by which neurons could induce activation of microglia, primary neurons were transfected with GFP‐(GR)100 and CXCL10, a regulator of chemotaxis and inducer of proinflammatory phenotypes of microglia was measured via ELISA. Results: Wild‐type GFP‐(GR)100 mice exhibited significant motor impairment and memory deficits, leading to mortality. Microglia were increased in GFP‐(GR)100 and found to be in an activated state. IL‐1β was elevated in the cortex and accompanied by an increase in active caspase‐1. Primary neurons transfected with GFP‐(GR)100 exhibited a significant increase in CXCL10. Genetic ablation of Nlrp3 in GFP‐(GR)100 mice conferred protection in motor function and memory, leading to a significant reduction in mortality. Furthermore, Nlrp3 ‐/‐ GFP‐(GR)100 mice did not exhibit increases in IL‐1β or active caspase‐1. Conclusion: Microglia mediated neuroinflammation is present in FTD/ALS. In vivo, significant neuroinflammation was noted by increased microglia density and activation, with elevated IL‐1β and active caspase‐1. In vitro studies indicated a mechanism by which neurons can induce proliferation and activation of microglia in response to FTD/ALS neuropathologies. Genetic ablation of Nlrp3 resulted in significant attenuation of FTD/ALS neuropathologies, leading to improvements in behavior and survival. These data implicate microglia mediated innate immune responses as a potent target for treatment of FTD/ALS.